Small-bowel bezoars in an infant following synbiotic ingestion: a novel case report - Ju Yeon Lee; Seo-Hee Kim (Pediatric Emergency Medicine Journal)
Bezoars in infants are rare owing to their limited dietary diversity. This report presents a novel case of multiple phytobezoars in the small bowel of a 3-month-old boy following ingestion of a synbiotic, a nutritional supplement combining probiotics (bacteria) and prebiotics (fibers that promote bacterial growth), which required a surgical intervention. Given the increasing use of synbiotics, the possibility of such bezoar formation should be considered, particularly in infants with underlying risk factors, such as congenital aganglionic megacolon.